Utilização de leveduras vivas no suplemento de novilhas em regime de semiconfinamento - Pedrini, Cibeli de Almeida (2020)
The objective of this study was to evaluate the use of live yeasts in diets of cross-heifers, submitted to the semi-confinement regime, the work was carried out at Fazenda Triângulo, located in the municipality of Eldorado, in Mato Grosso do Sul, in partnership with the Faculty of Agricultural Sciences at the Federal University of Grande Dourados (FCA-UFGD), in Dourados, where it lasted 60 days, from April to June 2019. 62 cross-heifers, 13 ± 1,5 months with average weight were used of 404,85±18,77 kg. The animals were divided in a completely randomized design into two experimental groups and remained in pasture areas of Brachiaria Brizantha cv. Marandu. The experimental treatments were: Control (CON: without inclusion of yeast in the semiconfinition); Live yeast (LEV: addition of live yeast of 15g / day); the supplement was formulated and adjusted according to weight gain, according to the NRC (2001) for beef cattle, with a 1,2% PC intake and ad libitum water supply. In the pasture data, the values were consistent with the transition period, with low quality, the observed protein values were 5,08% and 6,75% of the pasture areas of the CON and LEV groups, respectively. The results obtained in the present study showed that the experimental group LEV consumed 4,46 kg of supplement, 0,85 kg less than the CON group, but a performance of 0,11 kg more than the animals in the CON group, as well as better digestibility of starch present in the diet and carcass evaluation parameters. The live yeast showed positive results, improving the use of the diet and helping in the gains within the system, and increasing the profits of the property, concluding that it can be used as an additive in the supplementation of heifers in a semi-confined regime.